Integrating Digital Tools in Teaching Interpreting: Students’ Perceptions and Learning Outcomes at English Education Program, FBMB UNDIKMA - S., K. Dedy Sandiarsa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study investigates the integration of digital tools in interpreting instruction and examines its effects on students’ learning outcomes and perceptions. Conducted at the Faculty of Arts, Management and Business Management (FBMB), Universitas Pendidikan Mandalika (UNDIKMA), the research involved 77 fifth-semester students enrolled in the Interpreting course. A mixed-methods design was employed, combining quantitative and qualitative approaches. Quantitative data were collected through pre- and post-tests and a structured questionnaire, while qualitative data were obtained from interviews and classroom observations. Digital tools such as YouGlish, VoiceTube, TED Talks, and AI-based note-taking applications were integrated into interpreting lessons over six weeks. Results from paired-sample t-tests revealed a significant improvement in students’ interpreting performance after the integration of digital tools, with mean scores increasing from 67.47 to 79.36 (p < .001). Questionnaire results indicated very positive perceptions (M = 4.30), particularly regarding motivation, engagement, and perceived usefulness. Thematic analysis of interviews and observations further showed that digital tools enhanced students’ exposure to authentic materials, promoted learner autonomy, and increased confidence. However, challenges such as unstable internet connections and varying levels of digital literacy were also identified. The study concludes that integrating digital tools significantly enriches interpreting instruction by fostering multimodal learning, engagement, and self-regulation. The findings highlight the importance of incorporating technology into interpreter education and provide pedagogical implications for curriculum design, teacher training, and institutional support in EFL contexts.